Answer:
1
Step-by-step explanation:
(((a/b)^(-4))^0)=
((b/a)^4)^0)=
((b^4)/(a^4))^0=
1
(ANYTHING to the power of 0 is equal to 1)
Answer:
-8 hope this helps
Step-by-step explanation:
Answer:
f(x) = (x -(-3))(x -(-4))
Step-by-step explanation:
The function can be written as the product of binomial terms whose values are zero at the given zeros.
(x -(-3)) is one such term
(x -(-4)) is another such term
The product of these is the desired quadratic function. In the form easiest to write, it is ...
f(x) = (x -(-3))(x -(-4))
This can be "simplified" to ...
f(x) = (x +3)(x +4) . . . . simplifying the signs
f(x) = x^2 +7x +12 . . . . multiplying it out
Okay so you would use PEMDAS (parentheses, exponents, multiply, divide, add, and subtract) so there are no parentheses so you do the exponents
![{6}^{2} = 36](https://tex.z-dn.net/?f=%20%7B6%7D%5E%7B2%7D%20%20%3D%20%2036)
then you do the rest so 100+36=136 and then 136-9=127 so the answer is 127